The (positive) effect of macroeconomic crises on the schooling and employment decisions of children in a middle-income country - Schady, Norbert Reudiger 1967- (Policy research working paper, 2002)
Under some conditions, macroeconomic crises can have a positive effect on the accumulation of human capital because they reduce the opportunity cost of schooling. This has profound implications for the design of appropriate social protection policies.